2021
DOI: 10.1016/j.asmr.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The Top 50 Most-Cited Knee Arthroscopy Studies

Abstract: Purpose: To objectively identify the 50 most influential studies in knee arthroscopy and provide an analysis of their key characteristics. Methods: The Clarivate Analytics Web of Knowledge database was used to gather data and metrics of knee arthroscopy research. The search list was sorted by the number of citations, and articles were included or excluded based on relevance to knee arthroscopy. The information extracted for each article included author name, publication year, country of origin, journal name, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…The 50 articles were published out of twelve different countries. The dominant proportion of US studies ( n = 23) is consistent with similar bibliometric studies and is not unique to orthopedic specialties [ 1 , 3 , 19 , 35 , 36 ]. This could result in authors outside the US being read and cited less than US authors.…”
Section: Discussionsupporting
confidence: 63%
“…The 50 articles were published out of twelve different countries. The dominant proportion of US studies ( n = 23) is consistent with similar bibliometric studies and is not unique to orthopedic specialties [ 1 , 3 , 19 , 35 , 36 ]. This could result in authors outside the US being read and cited less than US authors.…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, studies by Murphy et al, 32 Moore et al, 30 and Barbera et al, 7 in orthopaedic knee, shoulder, and hip arthroscopy, respectively, found similar trends of predominantly level 4 and 5 evidence and fewer pieces of highimpact, level 1 research. This finding is encouraging for orthopaedic sports medicine and foot and ankle surgeons, as the state of the Achilles tendon pathology literature is very robust and consists of high-quality pieces of literature from which to learn and influence practice.…”
Section: Discussionmentioning
confidence: 59%
“…These analyses have been widely used in medicine. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Similar analyses have been performed in the fields of ecology, 31 biotechnology, 32 , 33 medical education, 34 soccer, 35 and various others. 36 , 37 , 38 , 39 The purpose of this study was to identify the 50 most highly cited research publications in the sport of basketball.…”
Section: Introductionmentioning
confidence: 84%